PELAKSANAAN PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) DI KOTA PEKANBARU TAHUN 2020 - Utari Khoirunnisa; Harapan Tua RFS (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The implementation of PTSL in Pekanbaru City in every process of land registration activities carried out is in accordance with the instructions and implementing rules that have been set, but in its implementation there are still obstacles that cause the phenomenon of not issuing land rights certificates because the subject and object do not meet the registration requirements. land, such as the subject is not willing to make a statement indebted to BPHTB and PPh and PTSL Products which is carried out only until the stage of collecting physical data. Due to the unavailability of the SHAT budget in the current year, the subject is unknown and the subject is not willing to participate in this PTSL program activity. This study aims to determine: 1) Implementation of Complete Systematic Land Registration (PTSL) Program in Pekanbaru City in 2020. 2) Factors that hinder the Implementation of Complete Systematic Land Registration (PTSL) Program in Pekanbaru City in 2020. This study uses the theory of Program Implementation according to The theory of G. Shabbir Cheema and Dennis A. Rondinelli (2020) which consists of environmental conditions, relationships between organizations, organizational resources, characteristics and abilities of implementing agents. The research method in this study is a descriptive qualitative method with data collection through observation, interviews and documentation. The informants in this study are the Land Budget Analyst Division (Planning Coordinator) and the PTSL Program Recipient Community. Data analysis using qualitative descriptive according to Miles and Huberman quoted by (Sugiyono, 2017) namely Data Collection, Data Reduction, Data Presentation and Conclusion Drawing. The results of this study indicate that the Implementation of the Complete Systematic Land Registration Program in Pekanbaru City in 2020 has not been maximized. This is because there are inhibiting factors, namely the lack of socialization carried out by BPN, objections to PPh and BPHTB and land owners from outside the city/district. Keywords: Implementation, Program, PTSL, Land Rights.